2018
DOI: 10.1177/0956462417748859
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recent unsuppressed viral load in HIV-1-infected patients in care on first-line antiretroviral therapy in South Africa

Abstract: Unsuppressed viral load (VL) in patients on antiretroviral therapy (ART) occurs when treatment fails to suppress a person's VL and is associated with decreased survival and increased HIV transmission. The objective of this study was to evaluate factors associated with unsuppressed VL (VL > 400 copies/ml) in patients currently in care on first-line ART for ≥ 6 months attending South African public healthcare facilities. We analysed electronic medical records of ART patients with a VL result on record who starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
36
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 22 publications
12
36
3
Order By: Relevance
“…Because adolescence is characterized by increasing cognition [ 35 37 ], the relationship between viral suppression and age among long-term survivors of HIV could be mediated by the impact of self-efficacy and self-competency and risk-taking on ART adherence [ 3 , 33 ]. Similar findings regarding age were also found in a study among people living with HIV in South Africa, whereby adolescents aged < 15 were more likely to have unsuppressed viral load (viral load > 400 RNA copies/mL) compared with older patients [ 38 ]. Indeed, studies have consistently reported that increasing age reduced odds of non-viral suppression in Uganda (≥ 1000 RNA copies/mL) [ 39 ] and in several countries across Europe (> 50 RNA copies/mL) [ 40 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Because adolescence is characterized by increasing cognition [ 35 37 ], the relationship between viral suppression and age among long-term survivors of HIV could be mediated by the impact of self-efficacy and self-competency and risk-taking on ART adherence [ 3 , 33 ]. Similar findings regarding age were also found in a study among people living with HIV in South Africa, whereby adolescents aged < 15 were more likely to have unsuppressed viral load (viral load > 400 RNA copies/mL) compared with older patients [ 38 ]. Indeed, studies have consistently reported that increasing age reduced odds of non-viral suppression in Uganda (≥ 1000 RNA copies/mL) [ 39 ] and in several countries across Europe (> 50 RNA copies/mL) [ 40 ].…”
Section: Discussionsupporting
confidence: 82%
“…Shorter duration on ART was associated with viral non-suppression, which is to be expected given the destruction of CD4 cells resulting from high viral replication. Although the relationship between viral non-suppression, immunological responses, and duration on ART is not always consistent [ 41 ], similar findings were reported in a South African study, which reported that adolescents who had been on ART between six and 12 months were more likely to have viral non-suppression (viral load > 400 RNA copies/mL) compared with those who had been on treatment longer [ 38 ]. In our study, a lower viral load at the time of initial clinic enrollment also predicted viral suppression, which is in line with mechanisms of ART action [ 3 ].…”
Section: Discussionmentioning
confidence: 54%
“…Shorter duration on ART is also associated with higher odds of viral non-suppression [ 12 ]. To identify patients with unsuppressed VL in need of adherence interventions and at risk of virologic failure, providers should prioritize VL testing after 6 months of ART [ 36 ] in accordance with WHO guidelines. Timely targeted adherence counseling decreases the risk of treatment failure and drug resistance, negating the need for more expensive second-line or third-line therapy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…historical first-line treatment (85% suppression rate) in Johannesburg subdistrict F. [20] The low CD4+ cell counts despite viral suppression could be indicative of slow CD4+ cell count recovery. [21] Just under three-quarters (72.4%) of our patients remained in care in the study sites over the reported period.…”
Section: Researchmentioning
confidence: 99%